Brainstorming in the STEM-integrated Project-based Learning: Systematic Literature Review - Retni S Budiarti; Asni Johari; Muhammad Rusdi; Evita Anggereini (Universitas Pendidikan Ganesha, 2026)
STEM-integrated project-based learning (PjBL) has become an important approach in modern education, but its implementation often faces challenges such as a lack of student creativity and collaboration. This phenomenon encourages the importance of research on the role of brainstorming methods in improving the effectiveness of PjBL-STEM. The purpose of this study is to analyze empirical evidence regarding the benefits of brainstorming in the context of PjBL-STEM and to identify challenges and solutions for its implementation. This study uses a Systematic Literature Review (SLR) method with a systematic analysis design on 40 selected articles from 175 initial articles obtained from Scopus, Google Scholar, and ERIC databases. The sample was selected based on inclusion criteria such as relevance, full-text availability, and publications in the last 10 years (2014–2024). The research instruments included the SLR protocol, the CASP evaluation tool, and network analysis using VOSviewer. Data were analyzed thematically and quantitatively to identify patterns and relationships between concepts. The results of the study are expected to provide practical guidelines for educators in designing effective PjBL-STEM, as well as theoretical contributions in the development of innovative learning models. The benefits of the research include enhancing students' 21st-century skills such as creativity, collaboration, and problem-solving, as well as strengthening learning motivation through project-based and STEM approaches.